(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The objective of this study is to enable the role of modern and advanced computerized information systems. The model or mechanism should be developed by collecting the necessary information about the taxpayers and the sources of the taxpayers’ income, on the basis of which the accuracy of the inventory process will be adopted. In addition to studies related to computerized information systems and showing their importance to the tax institution. To achieve the objectives of the study and to answer its questions, the researcher relied on collecting data and information on the subject on the literature and previous studies The secondary sources, which also formed the theoretical framework of the study, were obtained either as a practical framework for the study. The researcher used to collect the preliminary data by obtaining information about the actual tax experience as an example (quotations - customs permits) , And the researcher used personal interviews with tax specialists, field observations in the sections and branches of the General Authority for Taxation, as well as resort to the questionnaire as a "secondary" of the research, designed and offered to arbitrators to take the views and take out the final version of the appropriate proportion The questionnaire was distributed to the departments of the General Authority for Taxation, the Department of Statistics, the Department of Statistics, the Business and Occupations Section, the Real Estate and Real Estate Section, the Real Estate Transfer Section, and 97 " To a set of conclusions and recommendations related to computer information systems in the process of taxing and the most important: • Lack of ownership of the majority of the staff of the General Authority for Taxation in general and its branches in particular the scientific and practical high specialization in computerized information systems • Despite the existence of computers with physical and intangible materials, and with the members of the graduates of computer science departments at the General Authority for Taxation, but the tax information is not available and entered into the computer in a highly specialized software, for the purpose of storage and presentation and submission when requested in a timely manner • Adopting an objective mechanism to develop a phased strategy that will work on the computerization of the existing database available in the tax departments, in order to ensure the efficiency of its details with the requirements of the work, • Prepare plans and alternatives for the implementation of the tax inventory mechanism, through the adoption of software approved and suspended in the government, such as national card departments, nationality departments, traffic departments, real estate registration, logistics and other service